3D contact effects in fretting fatigue tests. (April 2022) - Vázquez, J.; Erena, D.; Navarro, C.; Domínguez, J.
Abstract: Fretting fatigue is a material damage phenomenon produced in mechanical contacts. This phenomenon mainly produces surface cracking, and depending on the fretting regime, surface wear. In the bibliography many different types of fretting tests, with different geometries have been proposed. This paper numerically analyses, via FEM models, some fretting tests with cylindrical pads and test specimens having different geometries that are frequently used in the literature. In such cases, non-negligible 3D effects are produced. The differences between the contact stress field obtained with different approaches are analysed and discussed. Highlights: The behaviour of some usual fretting fatigue test are analysed. Tests are simulated in 3D via FEM using the submodelling technique. It is shown that the contact surface stresses between those tests are quite different. An analysis of the potential crack initiation points through the thickness is performed.